Current challenges and prospects for the development of the Polish public procurement - Kania, Michał (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2023)
The article aims to identify measures that should be taken to create an effective model of Polish public procurement. The study addresses the impact of the COVID-19 pandemic, the war in Ukraine, and the European Union policies on climate change and technological developments, including aspects of the Fourth Industrial Revolution, on the Polish public procurement market. A dogmatic method is adopted. The current challenges and prospects of the Polish public procurement market are analysed from the perspective of the Public Procurement Law of 11 September 2019, which came into force on 1 January 2021. The study shows that the effective model of public procurement should be based, first and foremost, on increasing dialogue between the public and private sectors, increasing the implementation of so-called strategic procurement, and creating conditions for supporting the principle of competitiveness.